Hydrotherapy Effect on Drinking Water on Reducing Momentary Blood Sugar Levels in People With Diabetes Mellitus in The Working Area of Kalasan Health Center: Pengaruh Hidroterapi Minum Air Putih Terhadap Penurunan Kadar Gula Darah Sesaat pada Penyandang Diabetes Mellitus di Wilayah Kerja Puskesmas Kalasan - Riyadina, Muchlisyah; Budi Susilo, Catur; Endarwati, Titik (Poltekkes Kemenkes Yogyakarta, 2023)
Diabetes mellitus is one of the diseases that can be life threatening. Diabetes mellitus can cause the body difficulty in controlling blood sugar levels and even can cause the body's organs to not effectively use insulin. One of the standard non-pharmacological therapies to alleviate the problem is hydrotherapy of drinking water. The purpose of this study was to find out the hydrotherapy effect on drinking water on reducing momentary blood sugar levels in people with diabetes mellitus in the working area of Kalasan Health Center. This research is a quasi-experimental with pre-test and post-test control group design. This research was conducted in February - March 2023 in the working area of Kalasan Health Center. The total sample was 58 respondents with type 2 diabetes mellitus according to the inclusion and exclusion criteria, the respondents were divided into the intervension groups 29 and the control groups 29. The data were analyzed using Wilcoxon test and Mann – Whitney test. The results of data processing using the Wilcoxon test in the intervention group obtained p = 0.000 (p <0.05), while in the control group obtained p = 0.000 (p <0.05). In addition, the results of data processing in the Mann – Whitney test obtained p = 0.002 (p <0.05). The test result show that there is a hydrotherapy effect on drinking water on reducing momentary blood sugar levels in people with diabetes mellitus in the working area of Kalasan Health Center. Penyakit diabetes mellitus merupakan salah satu masalah kesehatan yang dapat mengancam nyawa. Penyakit diabetes mellitus dapat mengakibatkan tubuh kesulitan dalam mengendalikan kadar gula darah bahkan dapat menyebabkan organ tubuh tidak dapat menggunakan insulin secara efektif. Salah satu standar terapi nonfarmakologi untuk mengatasi masalah tersebut adalah hidroterapi minum air putih. Tujuan penelitian ini untuk mengetahui pengaruh hidroterapi minum air putih terhadap penurunan kadar gula darah sesaat pada penyandang diabetes mellitus di wilayah kerja Puskesmas Kalasan. Penelitian ini merupakan eksperimental semu (quasi eksperimen) with pretest and posttest control group design. Penelitian ini dilaksanakan pada bulan Februari – Maret 2023. Jumlah sampel 58 responden penyandang diabetes mellitus tipe 2 sesuai dengan kriteria inklusi dan ekslusi, responden terbagi dalam kelompok intervensi 29 dan kelompok kontrol 29. Analisa data menggunakan uji Wilcoxondan uji Mann – Whitney. Hasil olah data menggunakan uji Wilcoxon pada kelompok intervensi diperoleh p=0,000 (p < 0,05), sedangkan pada kelompok kontrol diperoleh p=0,000 (p < 0,05). Selain itu, hasil olah data pada uji Mann – Whitney didapatkan p=0,002 (p < 0,05). Hasil uji tersebut menunjukkan bahwa terdapat pengaruh hidroterapi minum air putih terhadap penurunan kadar gula darah sesaat pada penyandang diabetes mellitus di wilayah kerja Puskesmas Kalasan.